Proposed work plan to enhance the work values and teaching performance of kindergarten teachers in Ilocos Norte - Managad, Raquel V. (Laoag City : [s.n.], 2019)
The study developed a proposed work plan for the kindergarten teachers in the Schools Division of Ilocos Norte. Specifically, it assessed the profile of the respondents, level of work values, the mean work performance, significant relationship between work values and teaching performance, and significant difference between the work value patterns of kindergarten teachers when grouped according to profile. The study utilized the descriptive correlational design because it ascertained the significant relationship between work values and work performance of the kindegarten teachers in the Schools Division of Ilocos Norte particularly in the 1st Congressional District who were the respondents of the study.
Bibliography: pages 118-122.
CHED-La Union
Keywords: Teacher -- Morale